DESAIN INFRASTRUKTUR HIJAU BERBASIS RESAPAN UNTUK PENGELOLAAN DRAINASE PERKOTAAN BERKELANJUTAN DI KECAMATAN DENPASAR BARAT: Infiltration-Based Green Infrastructure Design for Sustainable Urban Drainage Management in West Denpasar District - Praganingrum, Tjokorda Istri; Wangsa, Anak Agung Ratu Ritaka; Putra, I Putu Mahesa Pramana (Ganec Swara, 2026)
Changes in urban spatial patterns characterized by increasing built-up areas, increasing population density, and decreasing catchment areas have increased the pressure on the urban drainage system in the city of Denpasar. West Denpasar District is one of the areas that experienced this condition, especially in Padangsambian Kelod Village which in recent years has faced local inundation and flooding at a number of points. This study aims to analyze the impact of changes in spatial patterns on urban drainage performance and formulate a catchment-based green infrastructure design as a more sustainable water management strategy. The research uses a descriptive qualitative approach through field observations, interviews, document reviews, and mapping of spatial pattern changes. The results of the study show that the increase in built-up area in West Denpasar District has increased surface runoff and increased the existing drainage load, thus triggering inundation, especially on Jalan Gunung Salak and Jalan Gunung Tangkuban Perahu. Efforts that have been made, such as channel normalization, construction of new drainage, and retention ponds, have not been fully effective because they are still oriented towards accelerating water flow. This research offers a green infrastructure-based drainage channel design through the addition of biopore infiltration holes at the bottom of the channel, the use of reinforced concrete, and erosion protection with riprap and vegetation. The design is not only geared towards increasing flow capacity, but also strengthening infiltration, filtering pollutants, and supporting the sustainability of urban drainage systems. This study confirms that drainage management in urban areas requires a paradigm shift from water drainage systems to water management systems based on catchment and ecological adaptation.